Stepwise Assembly of an Electroactive Framework from a Co6S8 Superatomic Metalloligand and Cuprous Iodide Building Units. Issue 55 (1st September 2020) - Freeman, Matthew B.; Edokobi, Ozioma D.; Gillen, Jonathan H.; Kocherga, Margaret; Dipple, Kathleen M.; Jones, Daniel S.; Paley, Daniel W.; Wang, Le; Bejger, Christopher M.
Abstract: The design of metal–organic frameworks (MOFs) that incorporate more than one metal cluster constituent is a challenging task. Conventional one‐pot reaction protocols require judicious selection of ligand and metal ion precursors, yet remain unpredictable. Stable, preformed nanoclusters, with ligand shells that can undergo additional coordination‐driven reactions, provide a platform for assembling multi‐cluster solids with precision. Herein, a discrete Co6 S8 (PTA)6 (PTA=1, 3, 5‐triaza‐7‐phosphaadamantane) superatomic‐metalloligand is assembled into a three‐dimensional (3D) coordination polymer comprising Cu4 I4 secondary building units (SBUs). The resulting heterobimetallic framework (1 ) contains two distinct cluster constituents and bifunctional PTA linkers. Solid‐state diffuse reflectance studies reveal that 1 is an optical semiconductor with a band‐gap of 1.59 eV. Framework‐modified electrodes exhibit reversible redox behavior in the solid state arising from the Co6 S8 superatoms, which remain intact during framework synthesis. Abstract : Superatom MOF : A heterobimetallic MOF containing two‐distinct cluster units was prepared using a hierarchical approach. The framework contains Co6 S8 and Cu4 I4 entities and exhibits reversible redox activity in the solid state.